2009
DOI: 10.1149/1.3212850
|View full text |Cite
|
Sign up to set email alerts
|

On the Performance of LiNi[sub 1/3]Mn[sub 1/3]Co[sub 1/3]O[sub 2] Nanoparticles as a Cathode Material for Lithium-Ion Batteries

Abstract: We report on the behavior of nanometric LiMn1/3Ni1/3Co1/3normalO2 (LiMNC) as a cathode material for Li-ion batteries in comparison with the same material with submicrometric particles. The LiMNC material was produced by a self-combustion reaction, and the particle size was controlled by the temperature and duration of the follow-up calcination step. X-ray diffraction, scanning electron microscopy, X-ray photoelectron spectroscopy, Fourier transform infrared, Raman spectroscopy, electron paramagnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
61
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 67 publications
(117 reference statements)
4
61
0
Order By: Relevance
“…7. The rate performance of the bare sample is found to be comparable to recently reported Li(Ni 1/3 Mn 1/3 Co 1/3 )O 2 combustion synthesis with a 900 • C anneal [3]. Even at a rate of 2.5 C (400 mA g −1 ), our bare sample maintains a capacity of 120 mAh g −1 .…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…7. The rate performance of the bare sample is found to be comparable to recently reported Li(Ni 1/3 Mn 1/3 Co 1/3 )O 2 combustion synthesis with a 900 • C anneal [3]. Even at a rate of 2.5 C (400 mA g −1 ), our bare sample maintains a capacity of 120 mAh g −1 .…”
Section: Resultssupporting
confidence: 84%
“…More recently, Sclar et al reported on Li(Ni 1/3 Mn 1/3 Co 1/3 )O 2 fabrication by self-combustion reaction. By tailoring the temperature during an annealing process, Sclar improved both the capacity and the rate capability of Li(Ni 1/3 Mn 1/3 Co 1/3 )O 2 [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a variety of materials have been developed to substitute all or some of the cobalt with other transition metals [10][11][12][13]. One viable LiCoO 2 replacement material is layered LiNi 1/3 Co 1/3 Mn 1/3 O 2 due to its high reversible capacity, superior safety, less toxicity and low cost [14][15][16]. Unfortunately, there are still two serious shortcomings hindering its further applications.…”
Section: Introductionmentioning
confidence: 99%